INFLUENCE OF CELEBRITY ENDROSEMENT ON PURCHASE INTENTION MEDIATED BY BRAND AWARENESS OF SKINTIFIC ON TIKTOK - Afrida dewinta; Bintoro Bagus Purmono; Nur Afifah; Barkah Barkah; Dody Pratama Marumpe (SEAN Institute, 2023)
In the current era, many skincare products have emerged. One of the skincare products that is popular and in great demand is Skintific. The large number of skincare products appearing has created intense competition between products. In the face of increasingly fierce competition, Skintific markets its products through celebrity endorsements to promote products. Increasing consumer confidence in a product will cause the product to become better known among the public, leading to increased product sales. The research aims to determine and analyze the influence of celebrity endorsement on purchase intention with brand awareness as a mediating variable for studies on Skintific products through social media TikTok. The data collection method uses a questionnaire with a research sample of 201 respondents. The sampling technique used was purposive sampling using the statistical tools Structural Equation Modeling (SEM) and AMOS 24. This research shows that Celebrity Endorsement has a significant positive impact on Brand Awareness. Celebrity Endorsement also has a significant positive impact on Purchase Intention. Brand Awareness also has a significant impact on Purchase Intention. Brand Awareness can mediate the influence between Celebrity Endorsement and Purchase Intention